If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + -9) = 0 Reorder the terms: 3x(-9 + x) = 0 (-9 * 3x + x * 3x) = 0 (-27x + 3x2) = 0 Solving -27x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(-9 + x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-9 + x)' equal to zero and attempt to solve: Simplifying -9 + x = 0 Solving -9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + x = 0 + 9 x = 0 + 9 Combine like terms: 0 + 9 = 9 x = 9 Simplifying x = 9Solution
x = {0, 9}
| 3+2t=13 | | 5x-2= | | 3x^3+3x^2-11x-10=0 | | 4.2(x-1)=9.8 | | (x)(x)(x)+4(x)(x)-25x-100=0 | | 25x-10= | | x^2+5x=x(x-11) | | -12=-7-3.5s | | 7xy+1xy=72 | | (x)(x)(x)+4(x)(x)-100=0 | | 6x+10= | | n=wsv | | 7(a+1)-3a=5+4(a-1) | | 2(x-7)=3 | | -18y=da | | 1.33x+2=-1 | | 1.33+2=-1 | | 2*-8.5+13.6=0.4*-8.5 | | 5(3-t)-(3-3t)=5 | | 8x^6+6x^3+7=0 | | 3x+11=25 | | r^2-15r+54=0 | | 4x+10y-8+4x-4y= | | x^2-x-110=0 | | 10-a+3a=6 | | 3n+8= | | 2*-8.5+13.6=0.5*-8.5 | | 3(7-y)-6*2=-21 | | 2.3g=7013 | | 5x+6a+7= | | 2x+.25x=54 | | 12w-8=28 |